School Management Health Diagnosis to Improve School Quality - Hartini, Nani; Triatna, Cepi; Herawan, Endang; Rosalin, Elin; Nurlatifah, Siti; Gunawan, M. Irvan (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to reveal how to detect school management ailments so that efforts to improve or prevent them can be known. It was conducted in two stages: model development and model testing. Model development was carried out through literature reviews, focus group discussions (FGDs) with experts in Education Administration and Management, and field data collection through closed questionnaires. The model testing stage involved testing indicators and FGDs with practitioners and associations of school principals and supervisors to validate the school management health indicators. The research was conducted in 36 middle schools (both public and private) in Cimahi City, West Java Province, with respondents including school principals, teacher representatives, school committee chairs, administrative staff representatives, and student representatives. The research results can predict an increase or decrease in school quality through the health of the six school management functions by 73.5%, with the remaining 26.5% determined by other factors.